Kontribusi Dukungan Sosial dan Konsep Diri Terhadap Motivasi Berprestasi Siswa di SMP Negeri Kecamatan Batang Kapas Pesisir Selatan - Dianto, Mori; Gistituati, Nurhizrah; Mudjiran, Mudjiran (Konselor, 2015)
This research was done because of phenomenon of the students’ low motivation to get the achievement at school. Self concept and social support from the teacher have a correlation for creating the students’ potential giftedness to get an achievement in learning. The role of the teachers, especially the teachers of guidance and counseling are needed in improving the students’ achievement at school in order to improve their learning achievement. This research has purpose to find the social support, self concept, and achievement motivation of SMPN Kecamatan Batang Kapas Pesisir Selatan. This research is also done for knowing the contribution of social support and self concept through achievement motivation of SMPN Kecamatan Batang Kapas Pesisir Selatan. This research used correlational approach which has purpose to know how is the contribution among the research variables. The population of the research is the students of SMPN Kecamatan Batang Kapas Pesisir Selatan. The amount of the population was 601 students. The sample of this research was 240 students. It had been taken by using simple random sampling technique. The instrument used was a questionnaire. The data was analyzed by using descriptive technique and the hypothesis testing was done by using path analysis. The result shows that: (1) social support is in the enough category with average score is 115.9 or 77.29 of the ideal score, (2)  the self concept is in the enough category with average score is 93.53 or 74.82% of the ideal score, (3) students’ achievement motivation is in the enough category with average score 114.4 or 76.27 of the ideal score, (4) the contribution of social support through the students’ achievement motivation is about 20.2%, (5) the contribution of self concept through the students’ achievement motivation is about 14.4%, and (6) the contribution of social support and self concept through students achievement motivation is about 25.7%